Distribution of air bubbles in the EDML and EDC (Antarctica) ice cores, using a new method of automatic image analysis - Ueltzhöffer, Kai; Bendel, Verena; Freitag, Johannes; Kipfstuhl, Sepp; Wagenbach, Dietmar; Faria, Sérgio H.; Garbe, Christoph S. (Journal of glaciology, 2010)
Air bubbles in ice cores play an essential role in climate research, not only because they contain samples of the palaeoatmosphere, but also because their shape, size and distribution provide information about the past firn structure and the embedding of climate records into deep ice cores. In this context, we present profiles of average bubble size and bubble number for the entire EDML (Antarctica) core and the top 600 m of the EDC (Antarctica) core, and distributions of bubble sizes from selected depths. The data are generated with an image-processing framework which automatically extracts position, orientation, size and shape of an elliptical approximation of each bubble from thick-section micrographs, without user interaction. The presented software framework allows for registration of overlapping photomicrographs to yield accurate locations of bubble-like features. A comparison is made between the bubble parameterizations in the EDML and EDC cores and data published on the Vostok (Antarctica) ice core. The porosity at the firn/ice transition is inferred to lie between 8.62% and 10.48% for the EDC core and between 10.56% and 12.61 % for the EDML core.